Analisis Pengaruh Impor dan Ekspor terhadap Laju Pertumbuhan Ekonomi di Provinsi Sumatera Utara (2014-2023) - Tri Rahayu; Ranti Delima Tobing; Ogin Syaputra Sinaga; Sam Deva Sinulingga (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the effect of exports and imports on the rate of economic growth in North Sumatra Province in the period 2014-2023. The method used in this research is regression analysis with secondary data that includes the value of exports, imports, and the rate of economic growth. The results showed that simultaneously, the value of exports and imports had no significant effect on the rate of economic growth. Although there is a relationship between exports and economic growth, the effect is not strong enough to have a significant impact. Therefore, a more balanced trade policy and more effective strategies are needed to improve the competitiveness of local products in the international market and support sustainable economic growth.